The Relationship Between Nutritional Status and the Incidence of Anemia in Adolescent Girls - Selvi Puji Rahayu; Tutut Pujianto (Ficco Public Health Journal, 2025)
Background: Nutritional status is a measure of a person's body condition that can be determined from the food consumed and the use of substances within the body. Anemia is a condition where the levels of hemoglobin, hematocrit, and the number of red blood cells are lower than normal values. Methods: This study used an analytic cross-sectional design with a sample of 80 female adolescents aged 12-14 years in junior high school. As the independent variable, nutritional status is calculated from the results of measuring weight and height, while the dependent variable is the incidence of anemia assessed by blood Hb levels. To analyze the correlation between the two variables, the Spearman Rank test was used at α = 5%. Results: The research findings showed that 71.3% of the subjects were in the normal nutritional status category, 13.8% were in the overweight category, and 10.0% were obese. The prevalence of anemia among the study subjects was 30.0%. The results of the correlation analysis yielded a p value = 0.825. Conclusions: It is concluded that there is no significant relationship between nutritional status and the incidence of anemia in adolescent girls.